2021
DOI: 10.1038/s41598-021-97401-5
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of European wildcats inhabiting the area between the Dinaric Alps and the Scardo-Pindic mountains

Abstract: Habitat fragmentation and loss have contributed significantly to the demographic decline of European wildcat populations and hybridization with domestic cats poses a threat to the loss of genetic purity of the species. In this study we used microsatellite markers to analyse genetic variation and structure of the wildcat populations from the area between the Dinaric Alps and the Scardo-Pindic mountains in Slovenia, Croatia, Serbia and North Macedonia. We also investigated hybridisation between populations of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…This is in line with the proposed role of Haemaphysalis ticks in the transmission of certain Hepatozoon species [ 23 , 24 ]. In particular, the possibility that H. concinna may play a vector role in the transmission of H. martis has already been mentioned in the context of unpublished previous data [ 10 ], and this is confirmed by the present results. It is noteworthy that only nymphs were found to be PCR-positive from a large set of various tick stages, indicating that in the case of transstadial transmission characteristic of Hepatozoon spp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with the proposed role of Haemaphysalis ticks in the transmission of certain Hepatozoon species [ 23 , 24 ]. In particular, the possibility that H. concinna may play a vector role in the transmission of H. martis has already been mentioned in the context of unpublished previous data [ 10 ], and this is confirmed by the present results. It is noteworthy that only nymphs were found to be PCR-positive from a large set of various tick stages, indicating that in the case of transstadial transmission characteristic of Hepatozoon spp.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, an isolated case of clinical infection has also been reported in a domestic cat from eastern Austria, the country neighboring western Hungary [ 34 ], and imported cases have also been reported in Germany [ 16 ]. Nevertheless, to the best of our knowledge, we report here the first case of autochthonous H. felis infection in wild cats north of the Mediterranean Basin (previously reported in Bosnia and Herzegovina [ 10 ]).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the Eurasian red squirrel was reported to harbour both ecotypes I and II in Western Europe (Belgium: Ruyts et al, 2017), ecotypes I, II and IV in Central Europe (Czech Republic: Lesiczka et al, 2021) and here it was identified for the first time as the host of ecotype-I in Hungary. Since all three host species of the zoonotic ecotype of A. phagocytophilum are well known for their urban or peri-urban presence (Fingland et al, 2021;Urzi et al, 2021;Wereszczuk et al, 2021), these results verify their role in the synanthropic enzootic cycle and epidemiology of granulocytic anaplasmosis and tick-borne fever.…”
supporting
confidence: 59%